ATYPICAL CELIAC DISEASE: A CLINICAL CASE - E. A. Roslavtseva; N. L. Pakhomovskaya; T. E. Borovik; A. S. Potapov; S. G. Khomeriki (Педиатрическая фармакология, 2012)
Celiac disease has traditionally been associated with severe malabsorption syndrome. Recent years it was shown that among children of preschool and school-age mild cases with atypical clinical picture were dominated that leads to diagnostic difficulties. Here we are citing an example of an atypical clinical/latent celiac disease course in a child aged 4.5 years.